Membangun Identitas Desa Wisata Tajuk melalui Website menggunakan Metode Waterfall : Analisis Komunikasi dan Strategi Digital Branding - Buana, Chandra Lukita; Pamungkas, Rifky Januar Adi; Muntaha, Rama Faisal; Umami, Zahrotul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Digital transformation plays a strategic role in introducing tourist villages, by utilizing digital technology to reach a wider tourism market. This study aims to build an integrated website that functions as a communication and branding medium for Tajuk Tourism Village. This website was developed using a waterfall software development model, with the main objective of increasing the visibility and attractiveness of Tajuk Tourism Village, as well as encouraging increased local income through village services and products. The result of this development is the Tajuk Smart Tourism website, which has been successfully created and hosted so that it can be accessed by the general public. This website uses XAMPP as a database manager, as well as HTML, PHP, CSS, Javascript, and Unity to present interactive content. This website not only provides practical information such as location, accommodation, and tourist activities, but is also able to build the image and identity of Tajuk Tourism Village as a superior tourist destination. The use of visual elements such as high-quality photos and videos, interesting narratives, and attractive designs, contribute to the creation of a virtual experience that changes tourists' perceptions of this village. In addition, the significant increase in visitors from 615 people per month to 900-1,200 people per month shows the success of the website in attracting more tourists. The income of the village community also increased rapidly, from 1 million rupiah per month to 6.6 million to 8.85 million rupiah per month. The website also provides great benefits to the local community, by opening up new opportunities in the tourism, homestay, and local product sectors. As a result, the website serves as an asset that supports village branding and increases its competitiveness in the digital tourism industry.